Hormonal replacement therapy complications in healthy post menopausal women - Valladares Gutiérrez, Elías (2015)
OBJETIVE: To identify the main complications associated with the use of hormone replacement therapy. MATERIALS AND METHODS: observational, cross-sectional and retrospective study of 514 healthy postmenopausal women receiving hormone replacement therapy with 0.625 mg conjugated equine estrogen plus 2.5 mg of medroxyprogesterone acetate per day, during the period between January 1998 and December 2002 . RESULTS: The mean age was 57.5 ± 5.75 years (range, 50-76). The body mass index was abnormal in 87.0% (n = 447) of patients, malnutrition and weight and was found in 12.5% (n = 64) and 0.6% (n = 3), respectively. The incidence of complications associated with hormone therapy was 40.1%. The most frequent were hypertriglyceridemia (31.7%), hypercholesterolemia (25.9%), heart disease (6.2%), endometrial hyperplasia (2.4%) and breast (2.4%) cancer, occurring more frequently (63.2%) in patients over 70 years. No case of pulmonary embolism occurred. CONCLUSIONS: The main complications of hormone replacement therapy in this group of women were hypertriglyceridemia, hypercholesterolemia, coronary heart disease, endometrial hyperplasia and breast cancer, which occurred more frequently after age 70.